2006
DOI: 10.1111/j.1744-7909.2006.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Composition and Assessment of Gracilaria lemaneiformis Bory

Abstract: The chemical composition, mineral elements, vitamins, free fatty acids and amino acid content of the edible red alga Gracilaria lemaneiformis Bory, grown in the sea near Nan'ao island, Guangdong Province, were analyzed in the present study. Gracilaria lemaneiformis Bory showed a total sugar content of 14.65%. The protein content was 21%, of which approximately 41% was determined to be essential amino acids (EAA). The major amino acid components were glutamic acid, leucine, arginine, and alanine. Of the EAA ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 10 publications
1
42
2
Order By: Relevance
“…A preponderance of these complex and structural carbohydrates consists of polysaccharides (Deng and Ji 1995;Matsui et al 2003;Wen et al 2006). A lot of studies have confirmed that algal polysaccharides have antioxidant and antitumor effects and improve immunity of organism (Deng and Ji 1995;Matsui et al 2003;Wen et al 2006).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…A preponderance of these complex and structural carbohydrates consists of polysaccharides (Deng and Ji 1995;Matsui et al 2003;Wen et al 2006). A lot of studies have confirmed that algal polysaccharides have antioxidant and antitumor effects and improve immunity of organism (Deng and Ji 1995;Matsui et al 2003;Wen et al 2006).…”
Section: Discussionmentioning
confidence: 96%
“…A lot of studies have confirmed that algal polysaccharides have antioxidant and antitumor effects and improve immunity of organism (Deng and Ji 1995;Matsui et al 2003;Wen et al 2006). Besides, this may also be caused by large amount of b-carotene and vitamin C in the seaweeds, as previously reported (Satoh et al 1987;Wen et al 2006;Yu et al 2006).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the chemical composition of Gracilaria species is reported for only a few species (Mollet et al 1998;Norziah and Ching 2000;Wong and Cheung 2000;McDermid and Stuercke 2003;Wen et al 2006).…”
Section: Introductionmentioning
confidence: 95%